2019
DOI: 10.1097/mpg.0000000000002390
|View full text |Cite
|
Sign up to set email alerts
|

Higher Sun Exposure is Associated With Lower Risk of Pediatric Inflammatory Bowel Disease

Abstract: Objectives:The incidence of pediatric inflammatory bowel disease (IBD) is increasing worldwide. Ecological studies show higher incidence in regions at higher latitude or lower ambient ultraviolet radiation; individual-level associations with sun exposure have not been assessed.Methods:We recruited children (0–17 years) with IBD from 2 large hospitals in Melbourne, Australia. Control participants were recruited from the day surgery unit of one of the same hospitals. Questionnaires provided data on demographics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…A recent meta-analysis confirms a latitude gradient in the prevalence of MS which may be growing stronger; this provides further evidence of the importance of environmental factors in disease pathogenesis [ 115 ]. In children, higher sun exposure was associated with a lower risk of developing inflammatory bowel disease in an Australian study (adjusted OR 0.94, P = 0.002 for each additional 10 min outdoors) [ 116 ].…”
Section: Human Healthmentioning
confidence: 99%
“…A recent meta-analysis confirms a latitude gradient in the prevalence of MS which may be growing stronger; this provides further evidence of the importance of environmental factors in disease pathogenesis [ 115 ]. In children, higher sun exposure was associated with a lower risk of developing inflammatory bowel disease in an Australian study (adjusted OR 0.94, P = 0.002 for each additional 10 min outdoors) [ 116 ].…”
Section: Human Healthmentioning
confidence: 99%
“…15,36 The exact reasons for the IBD being more common in the Northern hemisphere have not been determined yet, but most commonly hypothesized and investigated are sunlight exposure, vitamin D levels, urbanization process, Mediterranean lifestyle, and so on. 37-39…”
Section: Discussionmentioning
confidence: 99%
“…15,36 The exact reasons for the IBD being more common in the Northern hemisphere have not been determined yet, but most commonly hypothesized and investigated are sunlight exposure, vitamin D levels, urbanization process, Mediterranean lifestyle, and so on. [37][38][39] With regard to the individual incidences of CD and UC, results of various studies show different proportions of IBD types in the overall IBD incidence. Studies from France, Germany, Czech Republic, Spain, and England have found a higher incidence of CD, 10,28,34,[40][41][42] which is inconsistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…This deficiency is thought to be related to malnutrition, inadequate dietary intake, lower bioavailability as well as reduced sunlight exposure. Higher sun exposure in the previous summer or winter was associated with a reduced risk of developing IBD [4].…”
Section: Introductionmentioning
confidence: 96%